Contrast Induced Nephropathy, Risk, Prevention, and Imaging Alternatives - Ahmed, Sarfraz; Rehman, Hafeez Ur; Rabbani, Saima; Yousaf, Adnan; Najmuddin, Najmuddin; Safeer, Shahid Rizwan; Najam, Danyal (Journal of Neonatal Surgery, 2025)
Background: Contrast-induced nephropathy (CIN) is a leading cause of acute kidney injury, primarily induced by iodinated contrast agents used in diagnostic imaging. CIN is associated with poor patient outcomes, including increased morbidity, prolonged hospitalization, and long-term kidney damage, particularly in high-risk populations with pre-existing kidney dysfunction. Objectives: To assess the risk factors, prevention strategies, and alternative imaging techniques to reduce contrast-induced nephropathy in patients undergoing contrast-enhanced imaging procedures, focusing on kidney function and patient outcomes. Methods: This prospective study conducted at Radiology Bacha Medical Complex Gajju Khan Medical College swabi from jan 2024 to jan 2025.involved 150 patients undergoing contrast-enhanced imaging procedures, evaluating risk factors such as pre-existing renal disease, diabetes, and dehydration. Hydration protocols and pre-procedure medications were used for prevention. Renal function was assessed before and after the procedure using serum creatinine levels and eGFR. Alternative imaging options, such as MRI and non-contrast CT, were explored for high-risk patients. Data were analyzed using statistical tests with significance set at p < 0.05. Results:Of the 150 patients, 20 (13.3%) developed CIN post-procedure. The mean pre-procedure serum creatinine level was 1.2 ± 0.4 mg/dL, while it increased to 1.6 ± 0.6 mg/dL after the procedure (p < 0.05). The standard deviation for serum creatinine levels was 0.5. Patients with pre-existing renal dysfunction and diabetes had a higher incidence of CIN (p < 0.01). Hydration and pre-procedure medications significantly reduced the incidence of CIN (p < 0.05). Non-contrast imaging methods were effective alternatives in 12% of cases. Conclusion: Contrast-induced nephropathy remains a major complication in high-risk patients undergoing contrast-enhanced imaging. Preventive strategies, such as hydration and the use of pre-procedure medications, significantly reduce the risk. Alternative imaging methods, including MRI and non-contrast CT, offer safe options for patients at high risk of CIN, enhancing patient safety and reducing renal complications. Further studies are needed to optimize CIN prevention.